2017
DOI: 10.3389/fphar.2017.00210
|View full text |Cite
|
Sign up to set email alerts
|

Statin Therapy Is Associated with Reduced Risk of Peptic Ulcer Disease in the Taiwanese Population

Abstract: Although statin use may affect the severity of chronic gastritis and gastric cancer, no data exists about the relationship between statin therapy and risk of peptic ulcer disease (PUD) in patients. We investigated the effect of statin use and the incidence of PUD from the Taiwan National Health Insurance Research Database (NHIRD). A total of 35,194 patients records for medical claims were enrolled. We performed a population-based case-control analysis to compare the incidence of PUD in patients who were prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
(50 reference statements)
2
16
0
Order By: Relevance
“…We have recently reported that high serum cholesterol levels in humans leads to an increased risk of being infected with H. pylori and induction of pathogenesis [35,50]. A population-based case-control study revealed that in patients who were prescribed statins (cholesterol-lowering agents), there was a decrease in H. pylori infection, and a reduced risk of peptic ulcer disease and gastric cancer [51,52]. It has been reported that probiotics exhibit anti-obesity effects by lowering serum cholesterol [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that high serum cholesterol levels in humans leads to an increased risk of being infected with H. pylori and induction of pathogenesis [35,50]. A population-based case-control study revealed that in patients who were prescribed statins (cholesterol-lowering agents), there was a decrease in H. pylori infection, and a reduced risk of peptic ulcer disease and gastric cancer [51,52]. It has been reported that probiotics exhibit anti-obesity effects by lowering serum cholesterol [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…It was found to enhance gastric mucosal defense against indomethacin-induced gastric ulceration via increasing NO and PGE 2 levels, promoting gastric mucin release and providing antioxidant activity [57]. Recent evidences concluded that statin mitigate Helicobacter pylori-associated pathogenesis [58] and protect against peptic ulcer in patients [59]. Neb has pleiotropic effects as being vasodilator and anti-oxidative which provides preferable protection from gastric ulcer [23].…”
Section: Discussionmentioning
confidence: 99%
“…The DDD, recommended by the World Health Organization (WHO), was assumed to be the average maintenance dose per day of a drug and analyzed as described previously ( Lin et al, 2017 ). The cumulative DDD was calculated by deriving the total prescribed DDD of each type of statin, namely simvastatin (ATC C10AA01) and lovastatin (ATC C10AA02), for statin users.…”
Section: Methodsmentioning
confidence: 99%